1993
DOI: 10.1002/cjce.5450710306
|View full text |Cite
|
Sign up to set email alerts
|

Application of nanofiltration to separate salts from a hydrogen-sulphide scrubber solution

Abstract: Experiments were carried out using nanofiltration to separate salts from a hydrogen sulphide scrubber solution taken from an iron‐based liquid‐redox process. The scrubber solution used in these experiments contained organic chelating agents, iron, and various alkali metal inorganic salts (i.e., sulphates, thiosulphates, carbonates, and bicarbonates). The nanofiltration unit was equipped with monovalent ion‐selective membranes. Results indicated that the nanofiltration membranes retained organic materials and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…where it is assumed that elemental sulfur is the primary oxidized sulfur product (see also Jamaluddin et al 1993).…”
Section: Posttest Site Characterization and Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…where it is assumed that elemental sulfur is the primary oxidized sulfur product (see also Jamaluddin et al 1993).…”
Section: Posttest Site Characterization and Performance Evaluationmentioning
confidence: 99%
“…where it is assumed that elemental sulfur is the primary oxidized sulfur product (see also Jamaluddin et al 1993). The larger amount of hydrogen sulfide consumed in the field compared to that predicted from laboratory experiments is related to the rate of aforementioned Reaction 3 and residence time considerations (Thornton et al 2005).…”
Section: Posttest Site Characterization and Performance Evaluationmentioning
confidence: 99%
“…Results of nanofiltration to separate salts from the solution of the LO-CAT I autocirculation process have been published (Jamaluddin et al, 1993). It is reported that nanofiltration membranes retain organic materials and iron but allow ionic species to permeate.…”
Section: Lo-cat Z Autocirculation Processmentioning
confidence: 99%
“…Lahiere and Goodboy ( 1993) used ceramic alumina microfiltration (MF) membranes to treat the petrochemical wastewater streams containing precipitated heavymetals, organic solvent emulsions with solids, and aromatic oils. Jamaluddin et at. (1993) applied nonofiltration (NF) to separate salts from a hydrogen sulphide scrubber solution.…”
Section: Chemical and Physical Treatmentmentioning
confidence: 99%